(untitled) (Journal of Informatics Education and Research, 2025)
This research investigates the intricate interplay between escapism, procrastination, and social media engagement among the Generation Z population in India. The primary aim was to examine the potential mediating role of procrastination in the association between escapist tendencies and excessive social media consumption. A sample of 621 participants aged 18-25 completed self-report measures assessing these constructs. Mediation analysis revealed a significant full mediation effect, indicating that procrastination serves as a critical intermediary in the relationship between escapism and excessive social media usage. The Generation Z commonly known as the Gen Z population consists of people born after 1995 who are just entering the workforce. These findings therefore offer valuable implications for the next generation in the workforce specially from an organizational psychology and human resource management perspective, underscoring the potential consequences of escapist tendencies and procrastination on employee productivity and well-being in the workplace.